PERAN BANK SAMPAH ASSOPIAH DALAM PENGELOLAAN SAMPAH ANORGANIK DI DUSUN SUKAMAJU - Khasanah, Rokhayatun; Rahayu, Syifa Silvana Puspita; Suangga, Ghina Farah; Karwati, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. In order to reduce the amount of garbage dumped anywhere so that it becomes an environmental pollution that will affect health, Dusun Sukamaju's community is trying to have a landfill. The purpose of writing this dedication journal is to know the role of Assopiah's garbage bank in addressing the problem of inorganic garbages that accumulate in Sukamaju Dusun. The methods of coercion used in this dedication are program planning, coercive, evaluation and monitoring. The role of the Assopiah waste bank in the management of inorganic garbage in Dusun Sukamaju can be said to be very helpful, because even though it has only been active for one month, the Assopiya waste bank has been able to deposit more than 500 kg of waste to the central waste bank, thus it can be concluded that the existence of a waste bank at each site is very important and necessary to continue to dissocialize by all parties, because the responsibility to manage the garbages is a joint obligation, involving the active role of government, public figures, and the general public. Through self-awareness, communities can play a significant role by clearing the garbage and storing it in the trash. This action can be seen as an alternative solution taken by society in its effort to manage garbage. Keywords: The role of the garbage bank, management, inorganic waste.